2009
DOI: 10.1002/ajp.20765
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in cranial dimorphism in Macaca fascicularis

Abstract: This study examines latitudinal and insular variation in the expression of sexual dimorphism in cranial length in three geographical groupings of Macaca fascicularis. In addition, the relationship between cranial length dimorphism (CLD) and sex-specific size is examined. The results of the study identified a significant relationship between CLD and latitude for only one of the three geographic groupings. Sex-specific relationships between cranial length and CLD were detected. The pattern of these relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…If such an association between latitude and sexual dimorphism does exist in Macaca mulatta , it seems that it has less to do with the body size gradient (Pearson's correlation test between body mass and sexual dimorphism: r = 0.28, P = 0.55) than with latitude itself. Thus Rensch's rule is less likely to hold in Macaca mulatta , which is consistent with the conclusions of previous studies on intra‐ specific level dimorphism variation in this species [Blanckenhorn et al, ; Fernandez‐Duque, ; Schillaci, ]. Schillaci et al [] concluded that the intra‐specific dimorphism variation of M. fascicularis in Singapore and Thailand was mainly due to the resource availability at different sites rather than differentiation in male size selection, because the feeding ecologies of their studying populations were very different.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…If such an association between latitude and sexual dimorphism does exist in Macaca mulatta , it seems that it has less to do with the body size gradient (Pearson's correlation test between body mass and sexual dimorphism: r = 0.28, P = 0.55) than with latitude itself. Thus Rensch's rule is less likely to hold in Macaca mulatta , which is consistent with the conclusions of previous studies on intra‐ specific level dimorphism variation in this species [Blanckenhorn et al, ; Fernandez‐Duque, ; Schillaci, ]. Schillaci et al [] concluded that the intra‐specific dimorphism variation of M. fascicularis in Singapore and Thailand was mainly due to the resource availability at different sites rather than differentiation in male size selection, because the feeding ecologies of their studying populations were very different.…”
Section: Discussionsupporting
confidence: 85%
“…However, BMD alone does not suffice to distinguish M. m. brevicaudus from other southern‐ distributed subspecies. Correlations between latitude and sexual dimorphism were noticed in some previous studies [Albrecht, ; Schillaci, ]. In our study, this correlation is not significant (Pearson's correlation test: r = 0.59, P = 0.16).…”
Section: Discussioncontrasting
confidence: 58%
“…Despite a wealth of studies in other orders, clinal variation in primates and its environmental underpinnings is relatively unstudied, with existing research providing few generalities. For instance, the long‐tailed macaque exhibits a limited Bergmannian size cline but the pig‐tailed macaque does not (Schillaci, ). An east–west rather than Bergmannian trend was found in Geoffroy's tamarin (Natori & Kondo, ) and Brazilian tufted‐eared marmosets (Albrecht, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous study indicates that the cranial dimensions can show age-related changes with an increasing pattern from young adulthood (7.0 years) to mid-adulthood (13.3-19.0 years in males and 19.7-22.6 years in females) and then become stagnant from mid-adulthood to very old age (26.9 years or more) or increasing from young adulthood to very old age. 6,8 This study only used young adulthood macaques with the following results: the male CL is significantly greater than female (116.68 vs 102.50; p=0.000); the mean male BZB is significantly greater than the female (79.30 vs 69.70; p=0.001); the mean male CBN is significantly greater than female (63.40 vs 58.79; p=0.019); and the mean male CBL is also significantly greater than that of females (63.32 vs 57.55; p=0.001). Collectively, this shows that cranial dimensions in male Macaca fascicularis is greater than those of its female counterpart, which is similar to human beings.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this shows that cranial dimensions in male Macaca fascicularis is greater than those of its female counterpart, which is similar to human beings. 7,8,11,12 As for maxillofacial bones and skull base structures, a complete maxillofacial primary bones are observed in Macaca fascicularis, i.e. maxillae, mandible, small frontal bone, nasal bone, and zygoma along with complete skull base primary bones consisting of frontal bone, sphenoid bone, temporal bone, and occipital bone.…”
Section: Discussionmentioning
confidence: 99%